ANALISIS INTERAKSI SOSIAL ANAK DOWN SYNDROME DENGAN TEMAN SEBAYA DI SEKOLAH INKLUSI SD NEGERI BOTOK - Lazuardi, Himawan; Abadi, Reza Febri; Mulia, Dedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the social interactions of children with Down syndrome with their peers at the inclusive school of Botok State Elementary School. This study used a descriptive qualitative approach with homeroom teachers, peers, and assistant teachers as participants. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The results indicate that social interactions between children with down syndrome and their peers in the inclusive school environment are quite successful. Patterns of social interaction include cooperation, accommodation, assimilation, competition, and conflict. Barriers to social interaction include a lack of rapport between students with special needs and typical students, ongoing discrimination, and negative behavioral traits among children with special needs. Efforts to address social interaction issues include conducting outreach on children with special needs, creating inclusive learning spaces, and teaching social skills to children with special needs.